2023
DOI: 10.1111/odi.14489
|View full text |Cite
|
Sign up to set email alerts
|

The alcohol harm paradox and tooth loss among Brazilian older adults

Abstract: ObjectiveTo investigate whether the association between alcohol consumption and tooth loss is modified across socioeconomic positions (SEPs) in Brazilian older adults.MethodsWe conducted a secondary analysis using data of The Brazilian Longitudinal Study of Ageing (ELSI‐Brazil 2015–2016). Effect Measure Modification (EMM) analyses using multivariable Poisson regression models tested whether the association between heavy drinking and lack of functional dentition (FD) varies in magnitude and direction according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…The role of effect modification as an explanation for the AHP was addressed for all-cause, cardiovascular, and alcohol-attributable mortalities (Boyd, Sexton, et al 2021) and tooth loss (Oliveira, Pelissari, et al 2022). Such evidence should guide resource Schematic to interventions on alcohol consumption for those disadvantaged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of effect modification as an explanation for the AHP was addressed for all-cause, cardiovascular, and alcohol-attributable mortalities (Boyd, Sexton, et al 2021) and tooth loss (Oliveira, Pelissari, et al 2022). Such evidence should guide resource Schematic to interventions on alcohol consumption for those disadvantaged.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon, known as the "alcohol harm paradox" (AHP), has been investigated in distinct high-income settings and has gained attention in recent years (Boyd, Sexton, et al 2021). Specifically regarding oral health outcomes, heavy drinkers from lower-SEP groups were disproportionately affected by nonfunctional dentition (Oliveira, Pelissari, et al 2022). Nevertheless, the exact mechanisms linking SEP, alcohol intake, and oral health outcomes remain little explored (Hach et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to oral diseases and conditions, previous studies have shown contradictory associations between alcohol intake and dental caries, 7,8 periodontitis, 9,10 tooth loss 11,12 and oral health‐related quality of life (OHRQoL) 13,14 . Nonetheless, evidence has mainly focused on the volume or frequency of consumption to describe the exposure and have not taken into account potential effect modification by socioeconomic position (SEP) in these associations; hence, neglecting the role of drinking patterns 15 and the “alcohol harm paradox” 16,17 . The former describes a dimension of alcohol exposure that differs from the average volume of consumption, often defined in terms of heavy drinking episodes.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Nonetheless, evidence has mainly focused on the volume or frequency of consumption to describe the exposure and have not taken into account potential effect modification by socioeconomic position (SEP) in these associations; hence, neglecting the role of drinking patterns 15 and the "alcohol harm paradox". 16,17 The former describes a dimension of alcohol exposure that differs from the average volume of consumption, often defined in terms of heavy drinking episodes. The latter is the phenomenon that posits that disadvantaged groups suffer from higher rates of alcohol-related harm than their more advantaged counterparts, despite having similar or lower alcohol intake.…”
Section: Introductionmentioning
confidence: 99%